Transformative impacts: trafficking survivors for sexual exploitation and their involvement in an emancipatory study in Nepal - Dhungel, Rita (My University, 2016)
Trafficking of girls and women for sexual exploitations and their reintegration have become serious social issues in the world, particularly in Nepal, drawing the attention of local and international communities, including United Nations, government, academia, practitioners and activists. Nevertheless, the paucity of research on reintegration of trafficking survivors in the Nepalese context exhibits the need for further research. For example, in previous studies, the experiences of trafficking survivors in their reintegration have been examined and some strategies have been proposed through a qualitative approach. However, no studies have been conducted from social justice and feminist paradigms, and therefore the study was designed to bridge the gaps identified in academic investigations. Through the use of Participatory Action Research (PAR), the purpose for this study is to promote transformational/experiential learning opportunities to trafficking survivors and measure its transformative change. By using a number of PAR tools, eight trafficking survivors as co-researchers have examined under researched experiences of survivors on transformational learning opportunities and its implications to transformative impacts. For the purpose of the study, the survivors were significantly involved in analyzing data, mainly in categorizing and coding, however, a praxis (action-reflection-action) encouraging participants to engage in meaningful dialogues and actions, was executed as emancipatory research and liberatory educational tools throughout the study period. The results demonstrate that personal and social transformations were achieved, grounded in experiential evidence in personal narratives. Implications of the study are discussed in the conclusion.
Presented on November 25-26, 2016, at the "Second Asia Pacific Conference on Contemporary Research (APCCR)" held in Kuala Lumpur, Malaysia.
Keywords: actions; praxis; reintegration; survivors; transformation